Köpares syn vid förvärv av lantbruksfastighet i Dalarnas och Gävleborgs län - Persson, Thomas (2014)
Today's real estate buyers value the purchase different today compared to a decade back. Previously it was the return value that ruled the market. This has created problems when the broker must allocate the purchase price of the property's various elements, because non-monetary values such as forest for leisure, recreation, and the feeling of owing has increased in recent years and an increasingly important part in the valuation process. The assessed value can be a guide, but is perceived today to be stereotyped to put a fair value at the individual item.